Modern Clinical Methods of Prevention and Treatment of Eye Diseases - Hasanova Sabina Baratovna (American Journal of Biomedicine and Pharmacy, 2025)
Eye diseases represent a significant global public health issue, affecting individuals across all age groups and potentially leading to visual impairment or blindness. With the advent of advanced medical technologies, modern clinical methods have revolutionized both the prevention and treatment of ocular conditions. This article explores current clinical strategies used in ophthalmology, including pharmacological therapies, surgical innovations, and preventative approaches based on patient education and regular screening. It also emphasizes evidence-based interventions and highlights the role of multidisciplinary care in improving patient outcomes. The burden of eye-related illnesses is steadily growing, especially with the increasing prevalence of systemic diseases such as diabetes, hypertension, and autoimmune disorders. Ocular disorders not only lead to partial or complete loss of vision but also significantly reduce a person’s functional independence and psychosocial well-being. In recent years, ophthalmic science has witnessed remarkable breakthroughs, ranging from personalized pharmacological interventions to non-invasive and image-guided microsurgical procedures. This article critically explores contemporary clinical strategies for managing and preventing eye diseases by examining data from large-scale studies and regional clinical practices. It also sheds light on the integration of digital technologies like artificial intelligence and telemedicine in the early diagnosis and continuous monitoring of high-risk patients. The findings emphasize the necessity of adopting a multidisciplinary and community-centered approach to enhance patient outcomes and mitigate the socioeconomic burden of vision impairment.